No benefit of vorapaxar on walking performance in patients with intermittent claudication. (February 2022) - Tsai, Shirling; Liu, Yulun; Alaiti, Mohamad Amer; Gutierrez, Jorge Antonio; Brilakis, Emmanouil S; Banerjee, Subhash
Background: The effect of pharmacologic agents in improving walking and quality of life measures in patients with intermittent claudication (IC) is variable. The objective of this study was to investigate the effect of the novel antithrombotic vorapaxar on symptom status in patients with IC.Methods: The study was a multicenter, randomized, placebo-controlled trial wherein patients with IC were treated with either vorapaxar or placebo in addition to a home exercise program for 6 months. Walking performance and quality of life were assessed by graded treadmill test (GTT) and 12-Item Short-Form Survey (SF-12), respectively, at baseline and at 6 months. A total of 102 subjects were randomized across 12 centers.Results: Of the subjects randomized, 66 completed all study assessments and comprised the dataset that was analyzed. After 6 months, there was no significant difference between the vorapaxar and placebo groups in walking performance, as reflected by the GTT, or in quality of life, as reflected by the SF-12. There were no severe bleeding events in either group.Conclusion: This study found no benefit of vorapaxar in patients with IC and reiterates the need for future drug therapy studies that expand the benefits of supervised exercise therapy in patients with IC.ClinicalTrials.gov Identifier: NCT02660866